Engage your workforce - Russell, Linda (Infoline, 2010)
In this issue, you will learn the definition of employee engagement and why it matters and then explore the various facets that make up an engaged workforce. You will also learn helpful strategies for developing and strengthening employee engagement that will lead toward full engagement.